Acute effect of ischemic preconditioning on lactate accumulation, time-trial performance und vascular function - Bailey, T. G.; Birk, G. K.; Jones, H.; Gregson, W.; Atkinson, G.; Cable, N. T.; Green, D.; Thijssen, D. H. J. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
Repeated bouts of ischemia followed by reperfusion, known as ischemic preconditioning (IPC), protects against cardiac damage after a myocardial infarction or cardiac surgery. Recent studies have established that IPC also improves maximal exercise performance. In this study, we examined the hypothesis that the performance effects of IPC relate to changes in blood lactate accumulation (bLa) and endothelial function. In a randomised, crossover study, 13 healthy men performed exercise preceded by lower limb IPC (4x5 min 220 mmHg bilateral occlusion) or a sham occlusion (SHAM; 4x5 min 20 mmHg bilateral occlusion). Subjects performed a graded treadmill running test, with 5x3min submaximal stages (10-14 km/h), followed by increments of 1 km/h every 2 min until volitional exhaustion. Accumulation of bLa was examined at the end of each 3 min stage and the onset of blood lactate accumulation (OBLA) was calculated. Subsequently, subjects performed a 5-km time-trial (5kmTT). Brachial artery endothelial function was examined using flow-mediated dilation (FMD) prior to any exercise and immediately post 5kmTT. A novel covariate-controlling approach using Generalised Estimating Equations (GEE) was used to analyse the effects of trial (IPC vs. SHAM) and time on bLa and FMD. A students t-test was used to assess any differences in OBLA and 5kmTT performance. Data are described as mean (95% CI). Accumulation in bLa was 1.1 (0.6 to 1.5) mMol/l lower at 14 km/h (P=0.023) when exercise was preceded with IPC compared to SHAM. This coincided with a trend for delayed OBLA after IPC (mean diff. of 1.5 km/h, -0.18 to 3.87, P=0.071). After IPC, the 5kmTT was completed 36.0s (5.0 to 64.1s, P=0.027) faster compared to SHAM. In SHAM, FMD decreased from 5.1% (4.4 to 5.9) to 3.7% (2.6 to 4.8) post 5kmTT (P=0.02), whereas it was maintained in the IPC condition; 5.4% (4.4 to 6.4) and 5.7% (4.6 to 6.8, P=0.60), respectively. This is the first study to show that IPC improves 5kmTT performance and attenuates the rise in bLa observed during running exercise. This suggests that prior IPC allows for higher work-rates for a given increase in bLa concentration. IPC also prevented the typical decrease in endothelial function associated with strenuous exercise. Taken together, our findings provide novel insight to support a physiological basis for IPC as an effective pre-exercise intervention to improve running performance in healthy males.